ChemInform Abstract: Solar Powered Lithium‐Ion Battery Incorporating High Performing Electrode Materials. Issue 6 (20th February 2013) - Gopukumar, S.; Nithya, C.; Maheshwari, P. H.; Ravikumar, R.; Thirunakaran, R.; Sivashanmugam, A.; Dhawan, S. K.; Mathur, R. B.
Abstract A new high‐performance lithium ion battery with a graphite paper anode and a LiMg0.025Cu0.175Co0.8O2 cathode, which can be charged by solar power, delivers an energy output of 280 Wh/kg with a cycling efficiency of 97% over 500 cycles of the lithium ion cell.